Language Learning Strategy: Comparison of Online and Face-to-Face ESL Classrooms - Sheikh Kamaruzaman, Syarifah Syarina; Nor Azmi, Nadhirah; Zulkflee, Zulaikha; Prakas, Jashwaniee; Maniam, Mahendran (International Journal of Academic Research in Progressive Education and Development, 2023)
Awareness of students’ LLS is highly useful for teachers to make informed decisions in their teaching practice. Although numerous researchers on LLS have been done, there has been no research comparing Malaysian students’ LLS in online lessons and face-to-face lessons. It is of great importance to explore this because the practice of incorporating blended learning that combines both online and face-to-face lessons has been on the rise. As such, this study explored Malaysian students’ language learning strategies during both online and face-to-face lessons. Mixed-method research approach was employed in which the first is a 5-point Likert scale survey questionnaire that was adapted from Oxford’s (1990) SILL questionnaire. 60 upper form ESL students were selected through convenience sampling to respond to the questionnaire. Aside from that, semi-structured interviews were carried out on 6 respondents from the questionnaire survey in order to obtain comprehensive responses from the participants. The research instrument aims to answer two research questions; 1) What are the language learning strategies used by Malaysian ESL learners in online classrooms? 2) What are the language learning strategies used by Malaysian ESL learners in face-to-face classrooms? The data was analysed using IBM SPSS Statistics version 27 and the findings were analysed descriptively by interpretation of mean scores and standard deviation. The findings suggest that students mostly use metacognitive and cognitive skills in both online and face-to-face classrooms. However, students use more direct learning strategies including memory and compensation strategies in online classrooms. Whereas, in face-to-face classroom, students generally lean more towards indirect learning strategies such as affective and social strategies. These findings implied that both online and face-to-face classrooms allow students to employ different learning strategies which can be beneficial for their language development. Hence, learning and teaching instructions that include both traditional and technologically enhanced ESL lessons would positively impact students. Future research of wider scale that includes diverse populations particularly from the quantitative view point would greatly help in adding onto the findings of this research.